Design and development of Cu–Al–Ni shape memory alloy coated optical fiber sensor for temperature sensing applications. (September 2021) - Singh, Shalini; Karthick, S.; Palani, I.A.
Abstract: — This paper focuses on the development of copper-based shape memory alloy (SMA) coated optical fiber sensor. The developed sensors are having potential applications for condition monitoring in different systems. The Cu–Al–Ni (82%-14%–4%) SMA has been deposited on optical fiber with the help of flash evaporation. To have an efficient deposition, an in-situ fixture has been designed, which can induce strain and rotate the fiber to get a uniform coating. The samples are prepared by varying the rotational speed of the fixture between 24 and 36 rpm (rotation per minute) during deposition. The optical fiber deposited at a rotational speed of 24 rpm has achieved a maximum bending angle of 53°. The actuation behaviour has been investigated in detail for varying load and voltage. Also, the surface morphology, thickness measurement and thermal analysis of coated and uncoated optical fiber have been investigated in detail. A complete review of test results showing the characteristics and performance of plastic optical fibers after coating with shape memory alloy has been provided in this paper. Static structural analysis has been performed in ANSYS workbench to observe the stress and strain developed during the bending of SMA coated fiber. Highlights: Fabrication of the Cu based SMA optic fiber has been demonstrated. Enhanced actuation due to improvement of phase transformation range by Ni addition. The austenite transformation temperature was found to be As = 231 °C and Af = 250 °C. Temperature sensing for pipeline monitoring with coated fiber has been explored.